Aripiprazole-induced quasi-neuroleptic malignant syndrome: two case reports - Abdelgadir Hussein M. Osman; Joshua Wilkinson (Journal of Medical Case Reports, 2024)
Abstract Background Significant elevation of creatine kinase levels (above three digits) and leucocytosis in the absence of muscle rigidity, tremors, or autonomic dysfunction can pose a real challenge in the context of antipsychotic treatment as an early herald of neuroleptic malignant syndrome. Case presentation We present here two cases of adult male patients of Black British heritage, ages 51 years and 28 years, respectively. Both received a diagnosis of schizoaffective disorder and presented with massive increase of creatine kinase blood level after aripiprazole depot administration, one with pernicious increase associated with silent neuroleptic malignant syndrome, and the second with asymptomatic benign enzyme elevation. Conclusion Though aripiprazole use is less likely to cause neuroleptic malignant syndrome, on rare occasions it can produce massive symptomatic or asymptomatic increase in serum creatine kinase enzyme levels, raising the need for close monitoring, especially at the initial doses of the drug.